Some Remarks on Hittite Rituals: The Relation between Word and Object - Cambronero, Ana Arroyo (Altorientalische Forschungen, 2010)
In Hittite literature the word for ‘ritual’ actually refers to ‘magical ritual’, without, in many cases, a definition of what is understood with this expression. The processes involved in this sphere of human behavior are traditionally explained through Frazer’s ‘The Golden Bough’ and assume the existence of Eliade’s homo religious . However, there are some features, which remain without a clear explanation, and some conducts, like false omens, that cannot be clarified following those theses. Other theoretical approaches allow us to understand this features and this kind of considered “exceptions to the normal behavior”, which are really not so uncommon.